2020
DOI: 10.3390/cancers12082252
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glucose Metabolism to Overcome Resistance to Anticancer Chemotherapy in Breast Cancer

Abstract: Breast cancer (BC) is the most prevalent cancer in women. BC is heterogeneous, with distinct phenotypical and morphological characteristics. These are based on their gene expression profiles, which divide BC into different subtypes, among which the triple-negative breast cancer (TNBC) subtype is the most aggressive one. The growing interest in tumor metabolism emphasizes the role of altered glucose metabolism in driving cancer progression, response to cancer treatment, and its distinct role in therapy resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 222 publications
(288 reference statements)
1
105
0
Order By: Relevance
“…A Phase II clinical trial involving 164 patients was recently showed that in patients with HER2-metastatic breast cancer, addition of indoximod, the Indoleamine 2,3-dioxygenase 1 (IDO1) pathway inhibitor, to taxane did not improve PFS compared with taxane alone ( 300 ). The use of glucose metabolic inhibitors such as 2-deoxy-D-glucose (2-DG) and metformin in combination with chemotherapy has shown encouraging results in combating chemotherapy resistance ( 301 ). One patient with medullary breast cancer metastatic to lung and lymph nodes underwent extensive pretreatment (8 previous systemic treatment options) was reported to have a confirmed partial response (PR) with a duration of 65 days when treated with 45 mg/kg 2-DG every other week ( 298 ).…”
Section: Drugs Targeting Metabolism In Metastatic Breast Cancermentioning
confidence: 99%
“…A Phase II clinical trial involving 164 patients was recently showed that in patients with HER2-metastatic breast cancer, addition of indoximod, the Indoleamine 2,3-dioxygenase 1 (IDO1) pathway inhibitor, to taxane did not improve PFS compared with taxane alone ( 300 ). The use of glucose metabolic inhibitors such as 2-deoxy-D-glucose (2-DG) and metformin in combination with chemotherapy has shown encouraging results in combating chemotherapy resistance ( 301 ). One patient with medullary breast cancer metastatic to lung and lymph nodes underwent extensive pretreatment (8 previous systemic treatment options) was reported to have a confirmed partial response (PR) with a duration of 65 days when treated with 45 mg/kg 2-DG every other week ( 298 ).…”
Section: Drugs Targeting Metabolism In Metastatic Breast Cancermentioning
confidence: 99%
“…As principally described in the previous section, the metabolic reprogramming of cancer cells allows the switch from OXPHOS to less efficient aerobic glycolysis, regulated by various molecular events such as the HIF-1 regulatory pathway ( Figure 2 ) [ 11 , 68 ]. Dimerization of both HIF subunits (α and β) initiates the transcription of genes associated with increased glucose uptake and lactate production.…”
Section: Hypoxic Conditionsmentioning
confidence: 99%
“…Aberrant metabolism and elevated glycolytic rates in cancer cells are linked to various oncogenic processes such as proliferation, evasion of apoptosis, angiogenesis, and reprogramming of the tumor microenvironment [ 148 ]. Metabolomic studies reveal that cancers exhibit diverse metabolic phenotypes [ 148 ].…”
Section: Resveratrol: Its Impact On Intracellular Molecular Signalmentioning
confidence: 99%
“…Aberrant metabolism and elevated glycolytic rates in cancer cells are linked to various oncogenic processes such as proliferation, evasion of apoptosis, angiogenesis, and reprogramming of the tumor microenvironment [ 148 ]. Metabolomic studies reveal that cancers exhibit diverse metabolic phenotypes [ 148 ]. Malignant tumor cells utilize aerobic glycolysis to meet their increased glucose requirements in support of their rapid growth and proliferation; to this end, they overexpress glucose transporters (e.g., Glut1) [ 33 , 149 , 150 , 151 , 152 ].…”
Section: Resveratrol: Its Impact On Intracellular Molecular Signalmentioning
confidence: 99%
See 1 more Smart Citation